Does venture capital substitute Islamic profit and loss sharing contracts? theoretical analysis on Musharakah and venture capital - Ajmi, Hechem; Abd. Aziz, Hassanuddeen; Kassim, Salina (Universiti Putra Malaysia, 2020)
This paper emphasizes on the conflicts of interest between agents in order to assess whether venture capital can be a potential model of musharakah in imperfect markets. To achieve this purpose, this study opts for the financial contracting enforceability approach and Monte-Carlo simulation to identify the contract that maximizes the value of the firm subject to the enforcement constraint for the agent and the participation constraint for the principal, taking into account market frictions, and the two levels of the industrial shocks. Findings reveal that musharakah is the optimal contract for agents, subject to their constraints when the shock is low and high. In addition, the simulation results indicate that the increase in market frictions engenders higher profit-sharing ratio for the financier when venture capital and musharakah financings are used. The increase in the value of the firm in case of high shock is attributed to the increase in the profit-sharing ratios for both contracts to mitigate the selfish behavior of the agent. Therefore, the financier tends to require a higher profit-sharing ratio as a compensation for the severer information asymmetry.